NEGOSIASI MASKULINITAS DALAM RUANG DIGITAL: STUDI TENTANG MALE BEAUTY INFLUENCER DI INDONESIA - Yola Ninda Dwi Woro Dyah Sehnur (LENTERA: JOURNAL OF GENDER AND CHILDREN STUDIES, 2026)
The emergence of male beauty influencers challenges the gender binary that has traditionally associated beauty practices exclusively with femininity. In Indonesia, the circulation of the hashtag #MakeupIsGenderless has opened up space for men to showcase their makeup practices in the digital public sphere. This article aims to analyze whether the participation of male beauty influencers represents a form of gender empowerment or a rearticulation of hegemonic masculinity in digital culture. This research uses a qualitative approach through content analysis of the Instagram accounts of several Indonesian male beauty influencers. Using the concepts of hegemonic masculinity from Raewyn Connell and symbolic domination from Pierre Bourdieu, this article argues that while this phenomenon appears to deconstruct the gender binary, it simultaneously has the potential to reproduce masculine privilege. Men can enter spaces traditionally constructed as feminine without experiencing the structural oppression historically imposed on women. Thus, #MakeupIsGenderless functions not only as a discourse of liberation but also as an arena for renegotiating gender power relations in contemporary digital capitalism.